Intelligence activities of law enforcement agencies in the field of economic safety of Ukraine - Шаптала, Станіслав Миколайович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
The features of the intelligence activities of law enforcement officers in the field of economic safety of Ukraine as an element of anti-economic crime are considered.